Gram-positive bacteria with commercial potential from the gastrointestines of holothuria (Mertensiothuria) Leucospilota (Timun Laut) and Stichopus Horrens (Gamat) from Malaysian Waters - Kamarudin K.R.; Maryam Mohamed Rehan (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/ERA